Prevalence and spectrum of Cutaneous Tuberculosis in patients at Charlotte Maxeke Johannesburg Academic Hospital - Hargey, Naima (University of the Witwatersrand, Johannesburg, 2023)
Tuberculosis (TB) is a communicable disease that belongs in the top 10 causes of death worldwide. World Health Organization (WHO) indicated that 90% of the world’s TB cases occurred in 30 countries, with South Africa being one of the countries listed. Cutaneous TB comprises 1-2% of the extrapulmonary TB cases. Cutaneous TB is a chronic skin infection mainly caused by Mycobacterium Tuberculosis. The aim of this study was to investigate the prevalence and spectrum of Cutaneous TB in patients at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). A retrospective study of 69 patients were confirmed on histopathology with cutaneous TB. This was further sub-divided into true TB and tuberculid forms. These forms were correlated with histopathological and clinical findings as well as the patient’s HIV status. The average age (SD) of the 69 patients was 39(12). Females were more common than males in the study (ratio 7.625:1). The average disease duration (SD) of 17(22) months. Tuberculids (81.2%) were the most common form of cutaneous TB with Erythema Induratum (76.8%) being the most common tuberculid. The most common form of true cutaneous TB was that of Lupus Vulgaris (13%). Acid fast bacilli stains were the most common histopathological investigation done on tissue biopsies. Panniculitis (35.4%) was the most common histological feature. The most common clinical manifestation was that of nodules (59.3%). Few patients presented with polymorphic manifestations (20.3%). The lower limbs were the most common affected site in cutaneous TB particularly Erythema induratum (p<0.001). Other key findings for Erythema Induratum were its prevalence in females (p<0.001), histopathological findings of granulomas, vasculitis, panniculitus and AFB negativity (p<0.001). 33 of the 69 patients were HIV positive but the HIV status did not show a relationship with any form of cutaneous TB (p=0.971). Erythema Induratum patients who were HIV positive, were more likely to be on ARV’s (p<0.001). Despite South Africa being at the forefront of the HIV/TB epidemic, cutaneous TB remains uncommon. The advent of ARVs being prescribed to all HIV positive patients may have played a role in these patients presenting in a similar clinical and histopathological manner as HIV negative patients.
Research report submitted in fulfilment of the requirements for the degree of Master of Medicine in Dermatology, to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Tuberculosis (TB); World Health Organization (WHO); Mycobacterium Tuberculosis; Cutaneous TB; Charlotte Maxeke Johannesburg Academic Hospital (CMJAH); Tuberculids; Induratum; Erythema; Panniculitis; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education